Studi tentang Penanganan Siswa yang Terlambat Tiba di Sekolah oleh Guru BK SMA Negeri 13 Muaro Jambi - Dewi Fatimah (Medan Resource Center, 2021)
The purpose of this study is to know (1) pattern of student senior high school 13 Muaro Jambi arriving late, (2) factor that caused the late students of senior high school 13 Muaro Jambi, (3) the counselors handle against students who are late, (4) obstacles in addressing the welcome students arrive late and the conuselors efforts in addressing the barriers, (5) Students perseptions of late that has got the handling of counselors, and (6) the result of handling of school counselors of senior high school 13 Muaro Jambi towards student who arrive late.